An Appraisal of the Bentonite Flocculation Test in the Detection of Bovine Tuberculosis - Carrière, J. (1973)
In this further study, an exhaustive investigation into the value of the bentonite flocculation test in detecting tuberculosis in cattle was made on a group of 358 cattle, with known intradermal (ID) tuberculin reactions and with or without tuberculosis lesions. Bentonite sensitized with human old tuberculin (OT) and a purified BCG carbohydrate fraction (BCG-F1) were used. In the group of 126 cows with tuberculosis lesions, 113 were positive to the tuberculin ID test and there were also 113 positive reactions to the flocculation test using OT sensitized bentonite. Only 62 were positive using the BCG-F1 sensitized bentonite. Out of the 232 animals with no visible lesions, 114 reacted positively to the tuberculin ID test, 148 had a titer to the flocculation test using OT sensitized bentonite and 70 were positive when using BCG-F1 sensitized bentonite.